2019
DOI: 10.1111/mec.15292
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcodes expose unexpected diversity in Canadian mites

Abstract: Mites (Arachnida: Acariformes, Parasitiformes) are the most abundant and species‐rich group of arthropods in soil, but are also diverse in freshwater habitats, on plants, and as symbionts of larger animals. However, assessment of their diversity has been impeded by their small size and often cryptic morphology. As a consequence, published estimates of their species richness span more than two orders of magnitude (0.4–114 million). In this study we employ DNA barcoding and the Barcode Index Number (BIN) system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 76 publications
4
35
0
Order By: Relevance
“…Broad surveys of invertebrate soil diversity using HTS have commonly relied on markers of low species-level resolution and via eDNA extracted from small soil samples (Bahram et al, 2016; Wu et al, 2011; Zinger et al, 2019). Other studies have characterise specific groups of mites or springtails by individualised processing of specimens and relying on morphological assignment to generate species-level data (Caruso, Schaefer, Monson, & Keith, 2019; Ingimarsdóttir et al, 2012), but see also Young, Proctor, DeWaard, & Hebert (2019) on molecular species assignment. HTS data now greatly increase the potential of expanding both the number of species studied and the level of detail at which intra-specific variation for each is captured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broad surveys of invertebrate soil diversity using HTS have commonly relied on markers of low species-level resolution and via eDNA extracted from small soil samples (Bahram et al, 2016; Wu et al, 2011; Zinger et al, 2019). Other studies have characterise specific groups of mites or springtails by individualised processing of specimens and relying on morphological assignment to generate species-level data (Caruso, Schaefer, Monson, & Keith, 2019; Ingimarsdóttir et al, 2012), but see also Young, Proctor, DeWaard, & Hebert (2019) on molecular species assignment. HTS data now greatly increase the potential of expanding both the number of species studied and the level of detail at which intra-specific variation for each is captured.…”
Section: Discussionmentioning
confidence: 99%
“…However, they do not inform about colonisation and establishment success (effective dispersal) and possibly only pertain to a few highly dispersive species. Additionally, the dispersal potential may have been overestimated due to the low resolution of morphological species identification (Cicconardi et al, 2013) leading to perceived low turnover among sites, as evident from recent large-scale barcoding studies (Young et al, 2019). Our results at the community level thus raise doubts about a generalised dispersal advantage for small-bodied arthropods and instead indicate very small dispersal distances, even over evolutionary time scales, for the majority of species that make up the complex mesofauna communities of the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that inconspicuous and/or small taxa, often with a reclusive life style, show particularly high levels of cryptic diversity ( Von Saltzwedel, Scheu & Schaefer, 2017 ; Wagner et al, 2019 ). Mites are no exception, and indeed, their actual diversity seems to be vastly underestimated, even in common and easily recognizable taxa ( Navia et al, 2013 ; Young et al, 2019 ; Schäffer, Kerschbaumer & Koblmüller, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent phylogenetic studies on mites and metabarcoding studies based on environmental DNA suggest that the number of mite species currently recognized is a considerable underestimation of the true diversity, even for common taxa allegedly easy to identify to species level ( Navia et al, 2013 ; Young et al, 2019 ; Schäffer, Kerschbaumer & Koblmüller, 2019 ). As P. leontonychus has been reported to be associated with a large number of bark beetles, which themselves tend to show some preferences to particular tree genera ( Raffa, Gregoire & Lindgren, 2015 ), the question arises whether P. leontonychus is a truly widespread species with no host preference at all or whether it is a complex of cryptic species with specialization to particular hosts and trees as has been previously documented for uropodoid mites phoretic on bark beetles ( Knee et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, taxonomic identification based only on morphology can be difficult to virtually impossible or very time consuming when two or more species are morphologically highly similar. Indeed, there is increasing evidence that the diversity of recognized morphospecies does by far not reflect the true species diversity, especially in inconspicuous and small taxa [ 1 , 2 ]. In addition, certain life stages (i.e., eggs and larvae) or sexes are often morphologically indistinguishable among species [ 3 ], complicating inferences about species richness and ecological interactions.…”
Section: Introductionmentioning
confidence: 99%